Excision of Extensive Orbitozygomaticomaxillary Complex Tumors Combining an Intra- and Extraoral Approach With Transpalpebral Orbital Exenteration - Thomson, Amy E.; Rigby, Brittney E.; Geddes, Alexander T.; Soukup, Jason W. (Frontiers in Veterinary Science, 2020)
The junction of the bones of the orbit, caudal maxilla and zygoma intersect to form an anatomically intricate region known as the orbitozygomaticomaxillary complex (OZMC). Given the critical role of the OZMC in the structure, function and esthetics of the skull and midface, tumors in this region present unique challenges to the oromaxillofacial surgeon. Attempts to achieve histologically clean tumor margins in a cosmetically pleasing manner requires excellent intra-operative visualization. Additionally, minimized intra-operative and post-opertive complications is of paramount importance. In this manuscript we describe a combined intra- and extraoral approach to extensive tumors of the OZMC that incorporates orbital exenteration as a technique, which allows for excellent intra-operative visualization and mitigate intra- and post-operative complications. In addition, we describe our experience utilizing the technique in five clinical cases.